(untitled) (Global Journals of Research in Engineering, 2012)
Heavy metals in particular are a group of pollutants of major concern in the aquatic environment due to their toxicity. The need to find an inexpensive and effective method for heavy metals abatement from water becomes inevitable. Adsorption in very effectively used technique for this purpose but cost is an important parameter and the types of adsorbents conventionally used are expensive. The aim of this study is to use the tea waste as a low cost adsorbent for the removal of metal concentration in industry effluents. The effect of variation in different parameters like initial concentration of metals in solution, adsorbent amount and contact time were investigated. The adsorbent is very effective for lower concentration of metal solutions, and the adsorbance increases with increase in adsorbent dose. Around 96% removal of lead, 78% removal of nickel and 63% removal of cadmium is obtained using 0.5 gm of adsorbent and the efficiency is increased to 100% for Pb, 87% for Ni and 83% for Cd, by using 1.5 gm of the adsorbent. As this adsorbent is cheap and easily available, it can be used in little excess amount to obtain higher percentage of metal removal. A comparative study for removal efficiency for Pb, Ni, Cd is also discussed. The adsorbent prepared from tea waste is efficient and it is proposed that it can be conveniently employed as a low cost alternative in the treatment of waste water for heavy metal removal.